MANAGEMENT OF SCHOOL PRINCIPAL CHANGES IN ACHIEVING NATIONAL EDUCATION STANDARDS AT SDN 2 UEDELE TOJO DISTRICT TOJO UNA-UNA - Moh Ansar Hasan; Rizal Rizal Rizal; Surahman J Wilade (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
Management of School Principal Changes in Achieving National Education Standards at SDN 2 Uedele Tojo District Tojo Una-Una District. Elementary School Teacher Education Study Program, Department of Education, Faculty of Teacher Training and Education, Tadulako University. Advisor Dr. Rizal M.Pd. The problem in this study is about the Management of Change of School Principals in Achieving National Education Standards in SDN 2 Uedele Tojo District, Tojo Una-Una District. This type of research uses qualitative research with a descriptive approach, where the results of this study are described in the form of sentences and words. Bogdan and Taylor define qualitative research as research that produces descriptive data in the form of written or spoken words from people and observable behavior. This type of research is descriptive which aims to provide an overview of various problems based on the factors obtained from the object under study. The object of this research is the principal of SDN 2 Uedele and the location of this research is SDN 2 Uedele. The instrument used in this study was a questionnaire. The questionnaire used to find out how the management of school principal changes in achieving the national education standards at SDN 2 Uedele. The questionnaire consists of 15 questions using alternative answers, namely strongly agree (SS) = 4, agree (S) = 3, doubt (RG) = 2, disagree (TS) = 1. Based on research data and discussion of management changes in school principals in achieving national education standards at SDN 2 Uedele, it can be concluded that the change management of school principals in achieving national education standards is classified as "Good" criteria.